Chemical composition and antioxidant activity of Sorbus torminalis bark methanol extract - Leković, Aleksandra; Samardžić, Stevan; Radović Selgrad, Jelena; Kundaković-Vasović, Tatjana (Archives of Pharmacy, 2022)
Sorbus torminalis (L.) Crantz (Rosaceae), also known as wild service tree, is a deciduous tree widespread in central and southern Europe, north-western Africa, western Asia, the Balkan Peninsula and the Caucasus. Species of the genus Sorbus represent a rich source of polyphenols that are responsible for their numerous proven effects, including anti-diarrhoeal, anti-inflammatory, antidiabetic, antioxidant and anti-atherogenic effect. Accordingly, the bark of S. torminalis could have interesting composition and effects, however, data about this herbal drug is insufficient. Bark dry methanol extract (DER 9.74:1), obtained after successive extraction with cyclohexane and dichloromethane, was analyzed for antioxidant potential using DPPH and FRAP assay. Contents of total polyphenols, flavonoids and tannins were determined using spectrophotometric methods based on reaction with Folin-Ciocalteu reagent (FC), reaction with aluminum-chloride and adsorption by hide powder in combination with reaction with FC, respectively. LC-DAD-ESI-MS analysis was used for identification of main extract constituents. In DPPH test IC50 value 8.66±0.07 μg/mL was shown, while result of FRAP test was 3.01±0.11 μmol Fe2+/mg of dry extract. Contents of total polyphenols, flavonoids and tannins were 0.39±0.06 mg GA/mg of dry extract, 0.035±0.019% and 1.3±0.08%, respectively. By LC-DAD-ESI-MS analysis 25 compounds were detected among which procyanidins (dimers, trimers and tetramers) are dominant. The results of this study showed that dry methanol extract of S. torminalis bark is rich in procyanidins which potentially contribute to its antioxidant activity. Additional significant effects of this herbal drug and its isolated compounds should be investigated in future studies.